2005
DOI: 10.1007/s11010-005-5073-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on glycosaminoglycans and small leucine-rich proteoglycans production by skin fibroblasts

Abstract: Skin aging is characterised by a progressive deterioration of its functional properties, linked to alterations of dermal connective tissue. Whereas many studies have been devoted to collagen alterations during aging, the situation is less clear concerning glycosaminoglycans and proteoglycans. Particularly, the alterations of the expression of small leucine-rich proteoglycans (SLRPs), a family of proteoglycans strongly implicated in cell regulation, have never been studied. In the present study we measured glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
1
34
0
1
Order By: Relevance
“…Decrease of CS in aged sun-protected human skin, while KS and DS were increased, has been previously reported [34]; however, the other group reported that HA content was decreased in intrinsically aged skin in vivo, while no change in other GAG was found [35]. In addition, in cultured senescent fibroblasts, synthesis of total GAG was reported to be reduced, whereas synthesis of HS was reported to be increased [36,37], and other studies reported no change in DS and HS, increase in HA, and decrease in CS production in dermal fibroblasts of the elderly [38]. Recently, Tzellos et al [39] reported that mRNA expressions of several sulfated GAG-containing PGs, including versican, decorin, biglycan, perlecan, and syndecan-3 were less in aged sun-protected skin from behind ear lobe than in juvenile foreskin, implying that those less expression of PGs may result in less tsGAG amount in intrinsically aged skin.…”
Section: Discussionmentioning
confidence: 90%
“…Decrease of CS in aged sun-protected human skin, while KS and DS were increased, has been previously reported [34]; however, the other group reported that HA content was decreased in intrinsically aged skin in vivo, while no change in other GAG was found [35]. In addition, in cultured senescent fibroblasts, synthesis of total GAG was reported to be reduced, whereas synthesis of HS was reported to be increased [36,37], and other studies reported no change in DS and HS, increase in HA, and decrease in CS production in dermal fibroblasts of the elderly [38]. Recently, Tzellos et al [39] reported that mRNA expressions of several sulfated GAG-containing PGs, including versican, decorin, biglycan, perlecan, and syndecan-3 were less in aged sun-protected skin from behind ear lobe than in juvenile foreskin, implying that those less expression of PGs may result in less tsGAG amount in intrinsically aged skin.…”
Section: Discussionmentioning
confidence: 90%
“…While chronological or intrinsic aging is characterized by a reduction of skin thickness, loss of skin elasticity, collagen fibre degeneration, xerosis and wrinkle formation [21,22,23,24,25,26,27], extrinsic or photoaging caused by sunlight exposition leads to deep-wrinkled, dyspigmented skin and the formation of small dilated blood vessels near the skin surface (telangiectasia) [28]. It can be assumed that the most prominent physiological alterations in chronological and photoaging are localized in the dermis and caused by the metabolism of dermal collagen fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Although this possibility has not been tested, skin fibroblasts demonstrate increased HA synthesis with increasing age in vitro (Vuillermoz et al, 2005). Both HAS2 and HAS3 as well as CD44 are upregulated with aging in aortic smooth muscle cells (Vigetti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%